The place of wine in societies: the cultural perspective - Vítor Jo\~ao Pereira Domingues Martinho (ZBW – Leibniz Information Centre for Economics, 2019)
The wine has its own place in the societies, involving several dimensions, since the socioeconomic until the cultural level. In fact, in various countries and regions, the wine has a marked cultural presence, or because it is usual to consume wine at meals, or because it is an important ingredient in any meeting of friends. However, the cultural perspective of wine changes across regions and countries. In this framework the main objective of this study is to explore the cultural dimension of wine around the world. For that, it was considered 57 articles obtained from the Web of Science (all databases) for the topic “wine culture”. These documents were explored first with the bibliometric software VOSviewer and analysed after through literature review.
Keywords: 330; Bibliometric analysis; Literature review; Web of Science; VOSviewer